Decadal Variation of Dissolved Oxygen in the Lower Gangetic Delta Water - Abhijit Mitra; Subrata Trivedi; Sangita Agarwal; Sujoy Biswas; Prosenjit Pramanick; Sufia Zaman (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2015)
We analyzed the Dissolved Oxygen (DO) level in the surface water off Namkhana, a sampling station in the lower Gangetic delta region. Our three decade analysis in three different reasons (premonsoon, monsoon and postmonsoon) exhibits a decrease in the DO value with the passage of time. Based on the DO value we carried out a premilinary Water Quality Index (WQI) analysis using the average seasonal temperature of the study region. This index can be used as proxy to aquatic health in the study site, provided other relevant variables remain within the optimum range. The DO level varies as per the sequence monsoon > postmonsoon > premonsoon. The sudden rise of DO level and WQI during premonsoon 2009 is attributed to Aila, a super cyclone that passed across the lower Gangetic delta on 25th May, 2009 with a speed of ~110 km/hr.